PELATIHAN DAN PENDAMPINGAN IPM SMP UNISMUH MAKASSAR DALAM MENGATASI PERGAULAN BEBAS SISWA MELALUI GERAKAN JAMAAH DAN DAKWAH JAMAAH (GJDJ) DI KELURAHAN GUNUNG SARI KECAMATAN RAPPOCINI KOTA MAKASSAR. - Ulfa, Maria Ulviani; Sujariati, Sujariati (ADPERTISI, 2024)
Muhammadiyah Da'wah prioritizes renewal and fostering the religion of the people in a broad context, including the worldly aspects of mu'amalah. Through the establishment of charitable businesses such as schools, hospitals and orphanages, Muhammadiyah integrates Islamic teachings into everyday life. The Muhammadiyah Student Association (IPM) plays an important role in da'wah, especially in developing students through religious and social activities. However, there are challenges such as religious and health knowledge among IPM administrators that need to be addressed. Through the Jamaah and Congregational Da'wah Movement (GJDJ), training and mentoring are designed to increase understanding of religion and health, as well as overcome promiscuity among students. The methods used include needs analysis, module creation and validation, and training implementation. The results show increased awareness and active participation of students, strengthening of religion, and management capacity. Suggestions for improvement include increasing the quality of materials, use of technology, parental involvement, and regular evaluation. It is hoped that the implementation of these recommendations can improve the effectiveness of the IPM da'wah program in forming better student character.